FIGURATIVE LANGUAGE IN THE NIKI ZEFANYA EVERY SUMMERTIME SONG - Chintia Handayani (Jurnal Ilmiah Multidisiplin, 2022)
The problem of the research is what kinds of figurative language are found in Niki Zefanya’s song, title Every Summertime. The objective of the research is to find out the kinds of figurative language in Niki Zefanya’s song, title Every Summertime. This research used qualitative methods. By doing this research, the researcher used Perrine’s theory about various of figurative language as the basic in analysing the data. The source of the data is Every Summertime song lyric by Niki Zefanya. The data of this research is figurative sentence which contained in the song lyrics by Niki Zefanya. After being analysed, the researcher found allegory has 1 data, hyperbole is 2 data, personification is 1 data, synecdoche is 1 data, metaphor is 1 data, and metonymy is 1 data. The total of the data is 7 data.